Does Menses Affect the Risk of Blood Loss in Adolescent Idiopathic Scoliosis Patients Undergoing Posterior Spinal Fusion Surgeries?: A Propensity-Score Matching Study. Issue 16 (15th August 2020) - Chiu, Chee Kidd; Gani, Siti Mariam Abd; Chung, Weng Hong; Mihara, Yuki; Hasan, Mohd Shahnaz; Chan, Chris Yin Wei; Kwan, Mun Keong
Abstract : Study Design: Retrospective propensity score matching study. Objective: To investigate whether menses affect intraoperative blood loss in female adolescent idiopathic scoliosis (AIS) patients undergoing posterior spinal fusion (PSF) surgeries. Summary of Background Data: There were concerns whether patients having menses will have higher intraoperative blood loss if surgery were to be done during this period. Methods: This study included 372 females who were operated between May 2016 to May 2019. Fifty-five patients had menses during surgery (Group 1, G1) and 317 patients did not have menses during surgery (Group 2, G2). Propensity score matching (PSM) analysis with one-to-one, nearest neighbor matching technique and with a match tolerance of 0.001 was used. The main outcome measures were intraoperative blood loss (IBL), volume of blood salvaged, transfusion rate, preoperative hemoglobin, preoperative platelet, preoperative prothrombin time, preoperative activated partial thromboplastin time (APTT), international normalized ratio (INR), and postoperative hemoglobin. Postoperative Cobb angle and correction rate were also documented. Results: At the end of PSM analysis, 46 patients from each group were matched and balanced. The average operation duration for G1 was 140.8 ± 43.0 minutes compared with 143.1 ± 48.3 minutes in G2 ( P = 0.806). The intraoperative blood loss for G1 was 904.3 ± 496.3 mL and for G2 was 907.9 ± 482.8 mL ( P = 0.972). There was no significant difference in terms of normalized blood loss (NBL), volume of blood salvaged during surgery, preoperative hemoglobin, postoperative hemoglobin, hemoglobin drift, estimated blood volume (EBV), IBL per EBV and IBL per level fused ( P > 0.05). No postoperative complications were encountered in both groups. On average, the postoperative hospital stay was 3.5 ± 0.8 days for both groups ( P = 0.143). Conclusion: Performing corrective surgery during the menstrual phase in female AIS patients is safe without risk of increased blood loss. Level of Evidence: 4 Abstract : We conducted a propensity score match study and found that corrective surgery in female adolescent idiopathic scoliosis patients having menses was safe without increased risk of intraoperative blood loss.